Bio-based Green Solvents in Organic Synthesis. An Updated Review - Quadros, Gabriela T.; Valente, Livia C. L.; Abenante, Laura; Barcellos, Thiago; Hartwig, Daniela; Lenardão, Eder J. (Sustainability & Circularity NOW, 2025)
Solvents are essential for chemical reactions, formulations, and purification, with major use in paints, coatings, and pharmaceuticals. Global demand for solvents is expected to exceed 32 million metric tons by 2026. Solvents facilitate reactions, stabilize catalysts, assist in purification steps, and aid in the stability of reaction intermediates and transition states, which are crucial to the success of the chemical reaction. However, most of the solvents are petroleum-based, toxic, and environmentally harmful. The growing use of industrial solvents exacerbates the problems of waste and pollution. Therefore, there is an urgent need for alternative and sustainable solvents to replace current fossil-based ones. Green chemistry principles advocate for safer, renewable solvents to reduce environmental and health risks. The Sustainable Development Goals (SDGs) further emphasize clean water, innovation, and climate action. In this sense, bio-based solvents derived from renewable biomass feedstock are a promising alternative to petroleum-based solvents. While ethanol is widely used, newer options like carbohydrate-based solvents, terpenes, and natural deep eutectic solvents (NaDESs) are gaining attention. Other solvents, such as vegetable and animal oils and their derivatives, will not be discussed here, given that their benefits are limited and also that there is a scarcity of relevant literature. This review explores advancements made with regard to bio-based solvents over the past 5 years (from 2019 to the present). Over 70 studies are presented in this review regarding the use of bio-based solvents, highlighting their potential to replace conventional fossil-based ones, such as dichloromethane and toluene.
Keywords: Bio-based solvents; Green chemistry; Biomass; Organic synthesis